(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In recent years, returning farms are attracting attention as a new way of life from urbanites who are about to retire. Returning farming means that the population living in the city leaves the city and continues a new form of life in rural areas. In other words, the fever of returning farming and returning villages is increasing, and the present is called the era of returning farming. As interest in returning farms increases, it is essential to provide accurate information for a successful return to farming life. Therefore, in this paper, a set of returned farmers database was constructed to provide information related to returning farmers with improved reliability and accuracy. To this end, personal characteristic information of returnees and local environmental information were linked. In addition, a set of databases for returning farmers was constructed using population movement statistics and agricultural management database. In this paper, data necessary for service development were selected and collected. In addition, a total of three types of service scenarios were created according to the type of use of returnees, and information on customized policy projects for returnees were constructed. Finally, an exploratory analysis of the collected data was conducted. In other words, refinement work was carried out to build the utilized database set, and the database set was constructed according to the purpose of use. As a result, the agricultural support information and the agricultural management body database were used based on the basic characteristic information of the returnees to provide selective customized information and establish a database set to improve reliability. Through this, it is possible to provide a customized service for anyone interested in returning to farming to easily access the farming information database set and obtain related information.